2011
DOI: 10.1007/s12263-011-0240-z
|View full text |Cite
|
Sign up to set email alerts
|

Age-related changes in the mRNA levels of CYP1A1, CYP2B1/2 and CYP3A1 isoforms in rat small intestine

Abstract: It has been established beyond doubt that, as well as the liver, the small intestine is an important site of first-pass metabolism of numerous drugs, food components and toxic xenobiotics. However, there is not much information available about age-dependent changes of intestinal biotransformation pathways. In the present paper, we evaluated the relationships between intestinal cytochrome P450 complex activity and the age of animals. The study was carried out on male Sprague-Dawley rats (n = 5) from 5 age serie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 44 publications
1
9
0
Order By: Relevance
“…6). The high intestinal ability for detoxification in aged rats is also supported by the age-independent expression of P450s and age-dependent increase of UGT activity in rat intestine (Warrington et al, 2004;Bolling et al, 2011;Pałasz et al, 2012).…”
Section: Age-related Rat Hepatic and Intestinal Ces Expression 271mentioning
confidence: 83%
See 1 more Smart Citation
“…6). The high intestinal ability for detoxification in aged rats is also supported by the age-independent expression of P450s and age-dependent increase of UGT activity in rat intestine (Warrington et al, 2004;Bolling et al, 2011;Pałasz et al, 2012).…”
Section: Age-related Rat Hepatic and Intestinal Ces Expression 271mentioning
confidence: 83%
“…It has been reported that the expression of several metabolizing enzymes, e.g., P450 and UDPglucuronosyltransferase (UGT), is altered with aging in both rat liver and intestine. The rat hepatic expression of P450 decreases with aging (Warrington et al, 2003(Warrington et al, , 2004Yun et al, 2010), while ageindependent P450 expression has been shown in rat intestine (Warrington et al, 2004;Pałasz et al, 2012). With respect to UGT activity, no change or an age-dependent increase has been observed in rat liver and intestine, respectively (Lee et al, 2008;Bolling et al, 2011).…”
Section: Tablementioning
confidence: 98%
“…13,2022 For example: Factors such as menopause and old age are risk factors for bone diseases in humans, but are poorly modelled in younger rodents and require careful consideration of translational biomarkers in older rodents to ensure cross-species comparability. 2325 …”
mentioning
confidence: 99%
“…The small intestine is an important site of first-pass metabolism of numerous drugs, food components, and toxic xenobiotics. However, there is not much information available about age-dependent changes of intestinal biotransformation pathways (19). …”
Section: Expression Of Cyp In the Intestinementioning
confidence: 99%
“…However, it must be noted that there is a group of ultra-rapid metabolizers associated with CYP2D6, which results from gene amplification (9). Moreover, it seems that the activity of CYP complex in rat small intestine was not decreased by the aging process, so the high rate of oxidative metabolic reactions in intestinal mucosa can be maintained till the advanced life stage (19). …”
Section: Expression Of Cyp In the Intestinementioning
confidence: 99%